How Islamic Leadership and Islamic Worldview Play a Role in Restoring a Country's Economic Glory: Blibliometrical Analysis: Bagaimana Kepemimpinan Islam dan Pandangan Dunia Islam Berperan dalam Mengembalikan Kejayaan Ekonomi Suatu Negara: Analisis Blibliometrik - Susanto, Arva Athallah; Suprayitno, Aryadimas; Siti Zulaikha; Akhmad Kusuma Wardhana (Transformatif, 2025)
This bibliometric review aims to analyze the role of Islamic leadership and the Islamic worldview in restoring the economic prosperity of nations, particularly in countries with a predominantly Muslim population. The methodology involved a bibliometric approach, utilizing data from various sources, which were analyzed using the R Biblioshiny software. The analysis covered citation patterns, co-citation networks, and keyword analysis to identify trends, research gaps, and future directions in studies related to Islamic leadership and economic performance. The findings revealed 124 relevant documents, most of which were journal articles, indicating significant academic interest in this area. Key themes identified included Islamic leadership, worldview, and economic development. These publications originated from leading journals and prominent Islamic leadership and economics scholars. This review provided insights into academic contributions and studies' evolution by examining publication trends, citation patterns, and researcher collaboration networks. This review will serve as a foundation for future research exploring the relationship between Islamic leadership and economic prosperity.